Legality for Panji Buleleng Bali Traditional Herbal Medicine Through Phytochemical Laboratory Testing: Pendampingan Legalitas Produk UMKM Jamu Tradisional Desa Panji Buleleng Bali Melalui Uji Laboratorium Fitokimia - Luh Ari Arini; Anjar Tri Astuti; Irma Rahmayani; Luh Yenny Armayanti; Putu Sukma Kurniawan; Rahutama Atidira (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Panji Village, Buleleng Regency, is an area with a strong tradition of utilizing herbal plants and making traditional herbal medicine. However, limited public literacy regarding product quality standards, safety, and legality makes it difficult for traditional herbal medicine to compete in the modern market that demands quality assurance. This community service program aims to increase the capacity of Panji Village's herbal medicine MSMEs through literacy in simple laboratory tests, phytochemical analysis, and product development assistance. The activities were carried out using a participatory approach that included preparation, outreach, practical training, assistance, and evaluation through pretests and posttests, observations, and interviews. The results showed a significant increase in participants' understanding of herbal medicine quality testing, marked by a 35% increase in posttest scores and an 85% active participation rate. The phytochemical test results also confirmed the presence of active compounds such as flavonoids, alkaloids, tannins, and saponins, and the absence of heavy metal contaminants. In addition, 70% of MSMEs began utilizing digital media for promotion, and 92% of participants expressed satisfaction with the training activities. This program has proven effective in strengthening community scientific literacy, improving the quality of herbal medicine products, and encouraging MSMEs' readiness for legality and market competitiveness. Thus, this activity not only strengthens the preservation of local wisdom but also opens up opportunities for sustainable herbal-based economic development in Panji Village.